Gambaran dan Perubahan Pemahaman Masyarakat terhadap Mitigasi Kekeringan melalui Edukasi Sumur Resapan - Padang, Ostwald; Manek, Emanuel Grace; Sitepu, Dio Aldestra; Bachri, Rian Akmal; Triatmojo, Mohammad Afiandy; Aliansyah, Muhammad Yusuf (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Drought is one of the hydrometeorological disasters that significantly affects water availability, the environment, and the socio-economic lives of communities. The low level of public understanding regarding the causes and mitigation strategies for drought presents a major challenge in building environmental resilience. This study aims to describe and measure changes in community understanding of drought mitigation following an educational intervention on rainwater infiltration wells (sumur resapan) as a practical technical solution. The method employed was a pretest–posttest design using a Likert-scale questionnaire administered to 50 respondents. The results show a significant improvement in all measured aspects, including understanding of drought causes, mitigation steps, daily water-saving practices, and technical knowledge of constructing infiltration wells. Prior to the intervention, most participants demonstrated low levels of knowledge; after the educational session, there was a marked shift toward moderate to high levels of understanding. This participatory-based education proved effective in fostering awareness, preparedness, and trust in drought mitigation efforts through the implementation of infiltration well technology. These findings suggest the importance of sustained educational programs to strengthen community adaptation to climate change and water scarcity.